S wave attenuation structure on the western side of the Nankai subduction zone: Implications for fluid distribution and dynamics. Issue 10 (29th October 2014) - Takahashi, Tsutomu; Obana, Koichiro; Yamamoto, Yojiro; Nakanishi, Ayako; Kodaira, Shuichi; Kaneda, Yoshiyuki
Abstract We estimated the S wave attenuation structure in southwestern Japan and the western Nankai Trough by analyzing maximum S wave amplitudes at 4–8, 8–16, and 16–32 Hz with a correction term for apparent amplitude attenuation due to multiple forward scattering. Because the estimated attenuation (Q−1) in our tomographic study was much larger than Q−1 due to wide‐angle scattering, our estimated Q−1 was composed mainly of intrinsic attenuation. High‐attenuation areas (Q−1 > 1/300 at 4–8 Hz) were imaged beneath Quaternary volcanoes and south off Shikoku. Low (<1/1500 at 4–8 Hz) or moderate Q−1 (1/500–1/1000 at 4–8 Hz) was imaged beneath Shikoku and nonvolcanic areas of Chugoku. High and moderate Q−1 in and around Shikoku are located near the top of subducting Philippine Sea Plate. This correspondence implies that these high and moderate Q−1 reflect fluid in the subducting slab. By applying a theoretical model of attenuation in water‐saturated porous random media, we examined wave‐induced fluid flow induced by lower frequency (<1 Hz) seismic waves that may be related with triggering of nonvolcanic tremor by surface waves. Even though Q−1 structure in this study cannot fully explain the tremor triggering by wave‐induced fluid flow, large uncertainties of Q−1 in tremor zone suggest that high resolution imaging of Q−1 and random inhomogeneities would give some constraints for the spatial variation of permeability and other medium properties.